Killer triggers - Kenda, Joe (Blackstone Publishing, 2022)
A runner's fatal walk -- The serial killer next door -- The coming undone of a good man -- The choirboy gone bad -- A killer rental -- Murder in a mom 'n' pop shop -- A nest of vipers -- Twisted sisters -- Lowlifes deserve justice, too -- A killer pack -- Pulling the trigger.